Remote Island Students' Post-Compolsory Retention: Emplacement and Displacement as Factors Influencing Educational Persistence or Discontinuation - Anna Stewart; Joan Abbot-Chapman (Journal of Research in Rural Education, 2011)
Through ethnographic research using grounded theory we examined social, cultural and locational factors which result in low post-compulsory retention rates of remote island students. The research, conducted by an island "insider," followed a cohort of Australian students from Year 10 in a small island school off the coast of Tasmania to Year 11 in a secondary college on the Tasmanian mainland. The research investigated factors, identified by the students, that influenced their transition from Year 10, the final year of compulsory schooling, through to Years 11 and 12, and their persistence or discontinuation Attachment to the island as their home place and the emplacement of their cultural ties to family and community contrasted with the displacement experienced in the urban environment. This was felt especially strongly by indigenous students, who made up a third of the cohort. The research offers insights into the socio-spatial ambiguities experienced differently in different social contexts by students seeking a better education and the opportunities of urban living and at the same time longing for the island and island community. Findings are discussed in relation to research literature on the social construction of place, place attachment and the implications of place conscious education of rurally remote students.